Exploring Behavior-Oriented Decision Optimization among Logistics Service Supply Chain Managers in China: A Phenomenological Inquiry - Chunbin, Liu; Gumban, Gynnyn (Journal of Interdisciplinary Perspectives, 2025)
This study addresses the limited understanding of behavior-oriented decision optimization (BODO) among logistics service supply chain managers in China, despite its critical role in navigating the complexities of modern logistics. The research aimed to explore managers' lived experiences and decision-making behaviors employing BODO strategies. Using a Husserlian descriptive phenomenological design, the study was conducted from June 2024 to January 2025 with seven purposively selected logistics managers from Jiangxi Province, China. Data were gathered through semi-structured interviews and analyzed using Colaizzi’s method to extract significant statements and thematic clusters. Findings revealed seven key themes: (1) Navigating the dynamic logistics environment, emphasizing technology, collaboration, and sustainability; (2) The role of behavioral traits, such as visionary leadership and team synergy, in decision-making; (3) Behavioral excellence enhancing operational, organizational, and interpersonal dynamics; (4) Strengthening decision-making capacity through behavioral optimization; (5) Challenges in implementing BODO, including cultural and resource constraints; (6) Self-awareness as a foundational trait in refining decisions and communication; and (7) Strategic dynamics involving the integration of behavioral insights at multiple organizational levels. The results underscore that BODO is a multifaceted process shaped by personal, organizational, and contextual factors. Managers who effectively apply behavioral insights enhance decision quality, foster collaboration, improve customer experiences, and contribute to organizational adaptability and innovation. The study contributes to the literature by highlighting behavior as a critical dimension of decision optimization, offering practical insights for leadership development and strategic operations in logistics.